Make A Match Type Cooperative Model as an Effort to Improve Students' Critical Thinking Skills: Classroom Action Research in Elementary Madrasah - Marzuki (Jurnal Pengembangan Profesi Guru dan Dosen, 2024)
This study aims to improve students' critical thinking skill by applying the make a match model. This study is a classroom action research. The subjects of this study were elementary school students. Data were collected using observation and test techniques. The collected data were analyzed using descriptive statistical techniques. The results of the study indicate that the use of the problem based learning model can improve the learning outcomes of Islamic Religious Education on the material of Asmaul Husna examples in grade IV students of SDN 15 Meulaboh, Johan Pahlawan District, West Aceh Regency. Furthermore, there is an increase in each successive learning process from cycle 1 and cycle 2 as seen in the percentage of student learning outcomes. The results of teacher and student observations, the average value of student learning outcomes increased in the percentage of teacher activity observations in cycle 1 by 85% with good qualifications increasing in cycle 2 to 92% with very good qualifications.. Based on these results, the make a match model can be used as an alternative model in an effort to overcome the problem of low students' critical thinking skill.